2014
DOI: 10.3892/ol.2014.2692
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P-gp in acute myeloid leukemia and the reversal function of As2O3 on drug resistance

Abstract: To study the expression of P-glycoprotein (P-gp) and the reversal function of As2O3, the active ingredient of arsenic, on drug resistance in acute myeloid leukemia (AML) patients, P-gp and cluster of differentiation 34 (CD34) were examined in primary mononuclear and resistant cells, with or without As2O3. In addition, multidrug resistance gene 1 (MDR1) mRNA expression was investigated in K562/D cells and AML patients. In total, 28.6% of newly-treated (NT) patients and 59.1% of relapsed/refractory (RR) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Previous studies have revealed that conventional MDR leukemia cells exhibit increased sensitivity to As 2 O 3 instead of manifesting cross-resistance. This is possibly because As 2 O 3 is not a P-gp substrate and may even inhibit P-gp expression and activity (2)(3)(4)27). However, unlike other ADM-selected P-gp-overexpressing MDR tumor cells, including K562/ADM cells (2,3,27), the HL-60/RS cells established in the present study demonstrated cross-resistance to As 2 O 3 , which is a unique feature in MDR cells.…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…Previous studies have revealed that conventional MDR leukemia cells exhibit increased sensitivity to As 2 O 3 instead of manifesting cross-resistance. This is possibly because As 2 O 3 is not a P-gp substrate and may even inhibit P-gp expression and activity (2)(3)(4)27). However, unlike other ADM-selected P-gp-overexpressing MDR tumor cells, including K562/ADM cells (2,3,27), the HL-60/RS cells established in the present study demonstrated cross-resistance to As 2 O 3 , which is a unique feature in MDR cells.…”
Section: Discussionmentioning
confidence: 43%
“…MDR is currently a major and unresolved impediment to leukemia therapy (1)(2)(3)10). Although numerous extensive studies have investigated leukemia drug-resistance, regulatory pathways and intervention measures, the underlying mechanisms remain to be fully understood and few effective or clinically practical countermeasures have been identified (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations